Simulation Training to Improve Informed Consent and Pharmacokinetic/Pharmacodynamic Sampling in Pediatric Trials - Burckhardt, Bjoern B.; Ciplea, Agnes Maria; Laven, Anna; Ablonczy, László; Klingmann, Ingrid; Läer, Stephanie; Kleine, Karl; Dalinghaus, Michiel; Đukić, Milan; Breur, Johannes M. P. J.; van der Meulen, Marijke; Swoboda, Vanessa; et al. (Frontiers in Pharmacology, 2020)
Background: Pediatric trials to add missing data for evidence-based pharmacotherapy are still scarce. A tailored training concept appears to be a promising tool to cope with critical and complex situations before enrolling the very first patient and subsequently to ensure high-quality study conduct. The aim was to facilitate study success by optimizing the preparedness of the study staff shift. Method: An interdisciplinary faculty developed a simulation training focusing on the communication within the informed consent procedure and the conduct of the complex pharmacokinetic/pharmacodynamic (PK/PD) sampling within a simulation facility. Scenarios were video-debriefed by an audio-video system and manikins with artificial blood simulating patients were used. The training was evaluated by participants' self-assessment before and during trial recruitment. Results: The simulation training identified different optimization potentials for improved informed consent process and study conduct. It facilitated the reduction of avoidable errors, especially in the early phase of a clinical study. The knowledge gained through the intervention was used to train the study teams, improve the team composition and optimize the on-ward setting for the FP-7 funded "LENA" project (grant agreement no. 602295). Self-perceived ability to communicate core elements of the trial as well as its correct performance of sample preparation increased significantly (mean, 95% CI, p≤0.0001) from 3 (2.5-3.5) to 4 points (4.0-4.5), and from 2 (1.5-2.5) to 5 points (4.0-5.0). Conclusion: An innovative training concept to optimize the informed consent process and study conduct was successfully developed and enabled high-quality conduct of the pediatric trials as of the very first patient visit.